LATS‐regulated nuclear‐cytoplasmic translocation of SREBP2 inhibits hepatocellular carcinoma cell migration and invasion via epithelial–mesenchymal transition - Zhang, Feng; Gao, Jie; Liu, Xudong; Sun, Yaohui; Liu, Long; Hu, Bowen; Wang, Zhihui; Shi, Jihua; Guo, Wenzhi; Zhang, Shuijun (Molecular carcinogenesis, 2023)
Abnormal cholesterol synthesis plays a crucial role in the development of hepatocellular carcinoma (HCC). Sterol regulatory element‐binding protein 2 (SREBP2) is involved in cholesterol synthesis by translocating to the nucleus where it stimulates the transcription of genes encoding enzymes involved in the cholesterol synthesis pathway. However, the function and regulatory mechanism of SREBP2 in HCC remain unclear. In this study, we aimed to gain a better understanding of the effects of SREBP2 and its functional mechanism in HCC. In 20 HCC patients, we demonstrated that SREBP2 was highly expressed in HCC specimens, relative to their peritumoral tissue, and that higher expression correlated positively with a poor prognosis in these patients. Moreover, higher SREBP2 levels in the nucleus enhanced the occurrence of microvascular invasion, whereas inhibition of SREBP2 nuclear translocation by fatostatin markedly suppressed the migration and invasion of HCC cells via the epithelial–mesenchymal transition (EMT) process. The effects of SREBP2 were subject to functional activity of large tumor suppressor kinase (LATS), whereas inhibition of LATS promoted nuclear translocation of SREBP2, as observed in hepatoma cells and a subset of subcutaneous tumor samples from nude mice. In conclusion, SREBP2 enhances the invasion and metastasis of HCC cells by promoting EMT, which can be strengthened by the repression of LATS. Therefore, SREBP2 may serve as a novel therapeutic target for HCC.